Correlation between Hepatic Enzymes and Viral Load of HBV in Hepatitis B patients - Tabinda Ijaz, Fayyaz Ahmad, Muhammad Atif, Sajjad Ullah, Ahmed Bilal Waqar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatitis B virus is a causative agent of hepatitis B, and it is a severe global health issue. Aim: To investigate the increased level of aminotransferases and its association with viral load of HBV infected patients and to find the most sensitive and reliable technique for identification of HBV infection. Methods: This cross-sectional study included 198 patients of HBV. Blood samples were collected from these patients in serum tubes for detection of HBV by different techniques such as Immunochromatographic (ICT), Enzyme linked immunosorbent assay (ELISA), and whole blood was collected which was further processed for DNA extraction and real time PCR. Results: There were 64 female and 134 males in this study. All the patients were positive for HBV by the ICT method and also by ELISA method but for the RT-PCR out of these 198 patients 89(45%) were positive and 109 (55%) were negative. This study demonstrates no significant correlation between liver enzymes with viral load. The ICT test method is active and simple but not a precise and unique test also has no statistical correlation with viral load, but ELISA is correlated with viral load recognized by real time PCR. (P value=˂0.001, 95% Cl=0.40-0.69, r value =0.56). Conclusion: Our results concluded that the immunochromatographic technique is fast and easily available but not a precise and definitive test and has no statistical correlation with viral load, but ELISA is associated with viral load proved by RT-PCR. Real time polymerase chain reaction is the gold standard test for the detection of Hepatitis B virus infection. The practical implication of this study is that ICT technique is no longer a reliable technique for the diagnosis of HBV infection and the patients positive on ICT should be confirmed for HBV in PCR for both diagnostic and prognostic purposes. Keywords: Hepatitis B Virus, Liver enzymes, Immunochromatographic, Viral load, Enzyme linked immunosorbent assay